SPATIAL-TEMPORAL CHARACTERIZATION OF LAND USE VARIATION BETWEEN 1985 AND 2022 IN THE PIRANGA RIVER BASIN IN MINAS GERAIS (REMUNOM, 2025)
The dynamics of land use over time in river basins are crucial for understanding the factors that influence their variation and water availability. The Piranga River basin, an important tributary of the Doce River, is characterized by extensive areas of livestock farming and agriculture—activities that contribute to deforestation, increased erosion, and siltation of rivers. The primary objective of this study was to identify land use changes in the Piranga River basin in Minas Gerais between 1985 and 2022 and correlate them with variations in flow and rainfall patterns, using data from fluviometric stations and precipitation records. The methodology involved the use of geoprocessing and remote sensing tools, including images from MAPBIOMAS and vectors. The results revealed that, over the past four decades, the average annual land cover consisted of 29% native vegetation, 55% pastures, and 14% agriculture. Additionally, climatological normal data indicated no significant change in the rainfall pattern, but the flow rate of the Piranga River showed a declining trend over time. This trend may reflect poor land management, resulting in soil compaction and erosion, which increase surface runoff and reduce water infiltration. This situation exacerbates high flows during heavy rainfall events (floods) and diminished low flows during dry periods (leading to unsupplied water tables and spring droughts). The spatiotemporal analysis of imagery and hydrological data demonstrated that the economic management of land over the years has contributed to water imbalance in the basin. By highlighting the impacts of these changes, the study advocates for the adoption of sustainable land use practices, along with measures to restore degraded areas, particularly riparian forests and spring protection.